Critical role of glioma‐associated oncogene homolog 1 in maintaining invasive and mesenchymal‐like properties of melanoma cells. Issue 8 (11th July 2017) - Gunarta, I Ketut; Li, Rong; Nakazato, Ryota; Suzuki, Ryusuke; Boldbaatar, Jambaldorj; Suzuki, Takeshi; Yoshioka, Katsuji
Abstract : Cutaneous melanoma is the most aggressive form of skin cancer. This aggressiveness appears to be due to the cancer cells' ability to reversibly switch between phenotypes with non‐invasive and invasive potential, and microphthalmia‐associated transcription factor (MITF) is known to play a central role in this process. The transcription factor glioma‐associated oncogene homolog 1 (GLI1) is a component of the canonical and noncanonical sonic hedgehog pathways. Although GLI1 has been suggested to be involved in melanoma progression, its precise role and the mechanism underlying invasion remain unclear. Here we investigated whether and how GLI1 is involved in the invasive ability of melanoma cells. Gli1 knockdown (KD) melanoma cell lines, established by using Gli1 ‐targeting lentiviral short hairpin RNA, exhibited a markedly reduced invasion ability, but their MITF expression and activity were the same as controls. Gli1 KD melanoma cells also led to less lung metastasis in mice compared with control melanoma cells. Furthermore, the Gli1 KD melanoma cells underwent a mesenchymal‐to‐epithelial‐like transition, accompanied by downregulation of the epithelial‐to‐mesenchymal transition (EMT)‐inducing transcription factors (EMT‐TF) Snail1, Zeb1 and Twist1, but not Snail2 or Zeb2 . Collectively, these results indicate that GLI1 is important for maintaining the invasive and mesenchymal‐like properties of melanoma cells independent of MITF, most likely by modulating a subset of EMT‐TF. Our findings provide new insight into how heterogeneity and plasticity are achieved and regulated in melanoma. Abstract : The aggressiveness of cutaneous melanoma appears to be due to the cancer cells' ability to reversibly switch between phenotypes with non‐invasive and invasive potentials, and MITF is known to play a central role in this process. We found that Gli1 knockdown in melanoma cell lines exhibited markedly reduced invasion activity and underwent a mesenchymal‐to‐epithelial‐like transition without affecting MITF levels. This study indicates that GLI1 is important for maintaining the invasive and mesenchymal‐like properties of melanoma cells independent of MITF.